GRAMMAR AND ERUDITION IN SERVIUS’S COMMENTARY ON VIRGIL - Uría, Javier (Exemplaria Classica, 2018)
Alessandro Garcea– Marie-Karine Lhommé – Daniel Vallat (eds.), Fragments d’érudition. Servius et le savoir antique. ?Spudasmata. Studien zur Klassischen Philologie und ihren Grenzgebieten’, 168. Hildesheim-Zürich- New York: Georg Olms Verlag, 2016, 535 pp., ISBN 978-3-487-15433-6.